SEA SURFACE TEMPERATURES RECONSTRUCTION OF THE LAST 16,000 YEARS IN THE EASTERN MEDITERRANEAN SEA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2001)
A detailed study has been performed on two eastern Mediterranean box cores (BC02 and BC06) and on a southern Adriatic piston core (AD91-17) on the alkenone unsaturation ratio, a molecular proxy for past sea surface temperatures. The aim was to identify climatic events of the last 16 Ky, with particular attention on the conditions during formation of sapropel S1. All three temperature curves lack evidence for cooling in the Younger Dryas stadial and warming in the Boelling/Alleroed interstadial events. Just prior to the sapropel S1 base, SST cooled and increased by about 5°C during the sapropel deposition interval. Within sapropel S1, SST show a marked warming followed by a clear cooling. In the topmost intervals of the cores SST are mostly constant, but a warming event is always observed. This warming phase may correspond to the Medieval climatic Optimum (in the AD91-17 core) and to the Roman Optimum (in the box cores).